2023
DOI: 10.1038/s41598-023-38656-y
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and motivational differences between participants in analog and digital citizen science projects for monitoring mosquitoes

Berj Dekramanjian,
Frederic Bartumeus,
Helge Kampen
et al.

Abstract: Worldwide, citizen scientists help to map the distribution of native and introduced mosquito species in a variety of programs, contributing to environmental research and management decisions. Participant background, behavior, and engagement may vary depending on the project design, especially between those using digital apps and those using physical samples, which in turn may impact the quality and representativeness of the data collected. During the analysis of the responses to a survey directed at citizen sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…One impact of using automated species identification is that it opens up citizen science participation to a more diverse set of participants. For instance, a comparison of two similar citizen science projects focusing on mosquitoes—one analogue, where participants submit physical samples by post, and one digital, where participants submit photos through an app—showed that there was a significantly higher proportion of female, younger and non-academic participants in the digital project [ 51 ]. Also, in 2020, BirdNET—an app that uses artificial intelligence to identify birds based on sound—engaged more than 1.1 million participants compared to the 317,792 participants of eBird—an app where participation requires pre-existing identification skills [ 52 ].…”
Section: Technology As a Facilitator—making Citizen Science And Monit...mentioning
confidence: 99%
See 1 more Smart Citation
“…One impact of using automated species identification is that it opens up citizen science participation to a more diverse set of participants. For instance, a comparison of two similar citizen science projects focusing on mosquitoes—one analogue, where participants submit physical samples by post, and one digital, where participants submit photos through an app—showed that there was a significantly higher proportion of female, younger and non-academic participants in the digital project [ 51 ]. Also, in 2020, BirdNET—an app that uses artificial intelligence to identify birds based on sound—engaged more than 1.1 million participants compared to the 317,792 participants of eBird—an app where participation requires pre-existing identification skills [ 52 ].…”
Section: Technology As a Facilitator—making Citizen Science And Monit...mentioning
confidence: 99%
“…Monitoring our living world is not done solely by academic researchers or experienced naturalists but, when supported by the use of new technologies, can be done by anyone who has an interest, regardless of expertise. By changing the types of tasks and necessary skills, technologies can engage participants with diverse backgrounds, promoting inclusivity and widening societal engagement [ 51 ]. The development and inclusion of affordable technology in citizen science may help fill geographical data gaps, which is a major limiting factor of current biodiversity databases and large-scale predictions of biodiversity trends [ 97 ].…”
Section: Technology As a Transformer—rethinking Science And Collabora...mentioning
confidence: 99%